2005
DOI: 10.1136/thx.2004.026922
|View full text |Cite
|
Sign up to set email alerts
|

Rates of drug resistance and risk factor analysis in civilian and prison patients with tuberculosis in Samara Region, Russia

Abstract: Background: Tuberculosis (TB) and HIV rates continue to escalate in Russia, but true rates for drug resistance, especially multidrug resistant tuberculosis (MDR TB), are unknown. A study was conducted with the aims of identifying first line drug resistance, both in the civilian and prison sectors, for new and previously treated cases; and risk factors for the development of drug resistance. Methods: A cross sectional survey was undertaken of 600 patients (309 civilians, 291 prisoners) with bacteriologically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
5
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 17 publications
(4 reference statements)
6
100
5
6
Order By: Relevance
“…The SIT1 spoligotype is characteristic of the Beijing/W family, which is known for its frequent association with MDR, outbreaks and high emergence worldwide. The prevalence of Beijing isolates in Russia, both in prisons and in the community, and the high rate of MDR typical for this group have been recognized in a number of studies [5,6,23,[25][26][27]. Our results are consistent with this observation and demonstrate that the Beijing genotype plays an important role in the epidemiology of MDR-TB in civilian population of this high incidence region of the North-Western Russia.…”
Section: Resultssupporting
confidence: 90%
“…The SIT1 spoligotype is characteristic of the Beijing/W family, which is known for its frequent association with MDR, outbreaks and high emergence worldwide. The prevalence of Beijing isolates in Russia, both in prisons and in the community, and the high rate of MDR typical for this group have been recognized in a number of studies [5,6,23,[25][26][27]. Our results are consistent with this observation and demonstrate that the Beijing genotype plays an important role in the epidemiology of MDR-TB in civilian population of this high incidence region of the North-Western Russia.…”
Section: Resultssupporting
confidence: 90%
“…32 Patients with a history of imprisonment were also found to have a significantly increased risk of MDR-TB, as reported in three previous studies. 26,33,34 Finally, self-reported disability that was severe enough to prevent work was also positively associated with MDR-TB. However, this apparent association may be an artefact produced by the social security system in Belarus, which categorizes those who are receiving extended treatment for MDR-TB as disabled.…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, levels of drug resistance are very high, with nearly 14.7% of new patients resistant to at least one drug 2 Previous treatment of tuberculosis has been consistently reported as the risk factor within various clinical conditions and populations. [4][5][6][7][8][9][10] The present study also revealed that previous treatment of tuberculosis was strongly associated with MDR TB OR =2.799 (95 % CI 1.159 to 6.667) (p=0.020).According to the National Tuberculosis Programme's Nepal National Survey in 2007, MDR among new cases of TB is 2.9% and MDR among previously treated cases is at 11% thereby giving a ratio of approximately 4:1 for prevalence of MDR in these groups, 2 this pattern holds true in our study too. Lomtadze et.…”
Section: Discussionmentioning
confidence: 99%